The Relationship Workload and Perception of Compensation with Turnover Intention in Gen Z Employees Work as Baristas - Bilqis Rahmanda Hakim; Matulessy, Andik; Rini, Amanda Pasca (PT FORMOSA CENDEKIA GLOBAL, 2025)
Generation Z includes individuals born between the mid-1990s and 2012. Generation Z falls into the productive age, which is the age of 15-64 years, which is when Generation Z has begun to enter the workforce. This type of research is quantitative research using the Non-Probability Sampling method with a purposive sampling technique. In testing the first hypothesis, it is revealed that workload and perceptions of compensation with turnover intention have a significant effect. This proves a positive relationship between workload and perceptions of compensation with turnover intention in Gen Z employees who work as baristas. Based on the results of SPSS version 23, the F count is 226,796 with a sig level of 0.000 (p0.05), which means that the workload variable and the variable perception of compensation have a positive relationship with the turnover intention variable. Furthermore, in the workload variable with the turnover intention variable, there is a negative and significant relationship as evidenced by the significance value of 0.000 (p <0.05) with a calculated T value of -3.705. In the variable perception of compensation with the turnover intention variable, there is also a significant negative relationship, evidenced by the significance value of 0.000 (p <0.05) with a calculated T value of -19.386